Perancangan dan Implementasi Website Desa Menggunakan Laravel untuk Layanan Administrasi Desa - mujib, Ahmad; Syakti, Firamon; Khudri, Akhmad; Putra, Ade; Saputri, Nurul Adha Oktarini (LPPM Universitas Dinamika Bangsa, 2025)
Administrative and information services in Simpang Tais Village were previously managed manually, requiring residents to visit the office for document submissions such as domicile letters and business permits. This conventional process often caused queues, delays, and limited transparency. Information dissemination was also restricted to bulletin boards or oral communication, reducing its reach to citizens. To overcome these challenges, this study designed and implemented a village website using the Laravel framework and Agile methodology. The development process included planning, implementation, testing, deployment, and maintenance stages. The website provides key features such as online letter submission, verification by the village secretary, approval by the village head, and content management for news and announcements. Black-box testing confirmed that all modules functioned properly according to user needs. The results show that the system improved efficiency by reducing service time, enhanced transparency through online submission tracking, and increased accessibility to information. In conclusion, the Laravel-based website developed with the Agile approach effectively supports digital transformation at the village level and provides a foundation for future integration with broader e-government systems